Food Demand Projection and Consumption Patterns of Urban Households in Nigeria’s Kano State - Sadiq, Sanusi Mohammed; Singh, Invinder Paul; Ahmad, Muhammad Makarfi; Isah, Musa Ahmad; Alibaba, Ahmad (Journal of Agri-Food Science and Technology, 2023)
Changes in population and income are essential components for altering the pattern of food demand. In light of the importance of food demand analysis, this study set out to ascertain urban household consumption trends in Nigeria’s Kano State in order to forecast future demand levels for certain food items. This research contributes to becoming a basis for policymakers to increase food productivity. A household’s cross-sectional survey data elicited through a well-structured questionnaire complemented with an interview schedule from a total of 144 households chosen via a multi-stage sampling procedure was used for the study. The collected data were analyzed using both Linear Approximate/ Almost Ideal Demand System (LA/AIDS) and factor analysis models. Based on empirical evidence, households’ poor purchasing power is owed to high food inflation, which causes them to have low dietary diversity. Besides, the necessary and luxury goods, respectively, were rice, beans, spaghetti, and meat; and millet, yam, Irish potatoes, semovita, fish and groundnut. Meanwhile, maze, garri, and palm oil were established to be inferior commodities. Besides rice and semovita being everyday goods, they demand high price-sensitive commodities. Consequently, to maintain the status quo in the households’ welfare, the onus lies on policymakers to compensate consumers if there is a rise in the prices of local rice, indomie and groundnut oil. The study advises policymakers to increase the productivity of those food items projected to witness the steep-to-gentle rise in demand, and government should endeavour to adopt macro-economic policies with human-face so as to cushion/soften households’ economic hardship in the study area.